2010
DOI: 10.1523/jneurosci.2601-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α4* nAChRs is Necessary and Sufficient for Varenicline-Induced Reduction of Alcohol Consumption

Abstract: Recently, the smoking cessation therapeutic varenicline, a nicotinic acetylcholine receptor (nAChR) partial agonist, has been shown to reduce alcohol consumption. However, the mechanism and nAChR subtype(s) involved are unknown. Here we demonstrate that varenicline and alcohol exposure, either alone or in combination, selectively activates dopaminergic (DAergic) neurons within the posterior, but not the anterior, ventral tegmental area (VTA). To gain insight into which nAChR subtypes may be involved in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 50 publications
3
131
1
1
Order By: Relevance
“…This drug reduces not only nicotine dependence, but also alcohol consumption in rats (Steensland et al, 2007). Hendrickson et al (2010) showed this effect depends specifically on activation of alpha4 nicotinic receptors. In a mouse knockout line that did not express alpha4, varenicline did not reduce alcohol consumption.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This drug reduces not only nicotine dependence, but also alcohol consumption in rats (Steensland et al, 2007). Hendrickson et al (2010) showed this effect depends specifically on activation of alpha4 nicotinic receptors. In a mouse knockout line that did not express alpha4, varenicline did not reduce alcohol consumption.…”
Section: Discussionmentioning
confidence: 98%
“…Alcohol causes the increase of the neurotransmitter acetylcholine (Ericson et al, 2003). Acetylcholine activates nicotinic receptors, which in turn modulate the dopaminergic activation that is associated with drug reward response (Hendrickson et al, 2010; Soderpalm et al, 2009). In addition to many associations with nicotine dependence and smoking behaviors, CHRN subunit genes, particularly CHRNA4 and CHRNB2 , have also been implicated in alcohol and other substance use, and CHRN gene variants may contribute to both conditions (Schlaepfer et al, 2008a, 2008b; Wang et al, 2009; Tuesta et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in α6 and α5, but not β3, KO mice, high doses of EtOH-induced sedation was enhanced [28,29] . In addition, α4 KO mice show significantly less acute EtOH consumption to high (20%) but not low (2%) concentrations of EtOH [30] . Considering nAChR subunit compensation in a nAChR KO mouse background, these results collected from nAChR KO mice will need to be verified using shRNAs to knock-down nAChR subunits in discreet brain regions, and these data must also be interpreted with pharmacological evidence.…”
Section: Impact Of Nachrs In Etoh Reward and Dependencementioning
confidence: 90%
“…For example, the mammalian genes that code for the α6 and β3 subunits of the nAChRs (Chrna6 and Chrnb3, respectively) are located adjacent to one another on human and mouse chromosome 8. These two subunits have gained special attention for their expression in the VTA, their mRNA increase in the VTA after acute exposure to EtOH [30] , and their roles in regulating EtOH-induced increase in DA release [26] . More importantly, human genetic studies have shown that variation in these genes is associated with alcohol phenotypes [32] .…”
Section: Impact Of Nachrs In Etoh Reward and Dependencementioning
confidence: 99%